2014
DOI: 10.5301/ejo.5000460
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thinning in Pseudoexfoliation Syndrome Detected by Enhanced Depth Imaging Optical Coherence Tomography

Abstract: In PEX syndrome, there is choroidal thinning subfoveal, temporal, and nasal to the fovea on EDI-OCT. Decreased choroidal thickness, probably due to increased vascular resistance, and reduced blood flow, is seen in PEX syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
1
12
0
2
Order By: Relevance
“…[62496364] More recently, PEX and PEXG eyes have been found to have significantly lower posterior choroidal thicknesses, thought to be related to increased vascular resistance, compared to fellow unaffected eyes and healthy control eyes. [656667686970] As we better understand the molecular makeup of pseudoexfoliation material and its influence on the eye, it will be interesting to evaluate its role in glaucomatous optic neuropathy in PEX patients.…”
Section: Discussionmentioning
confidence: 99%
“…[62496364] More recently, PEX and PEXG eyes have been found to have significantly lower posterior choroidal thicknesses, thought to be related to increased vascular resistance, compared to fellow unaffected eyes and healthy control eyes. [656667686970] As we better understand the molecular makeup of pseudoexfoliation material and its influence on the eye, it will be interesting to evaluate its role in glaucomatous optic neuropathy in PEX patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of spectral optical coherence tomography (SD-OCT) systems, it is possible to capture the image of the full-thickness of the choroid in vivo [ 9 ]. Goktas et al have found that the macular choroidal thickness in patients with pseudoexfoliation syndrome is lower than that of healthy individuals [ 10 ]. In a study evaluating macular choroidal thickness in the patients with PEX glaucoma, Bayhan et al found the choroidal thickness in the nasal region to be thinner compared with the control group [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the mean SCT in the PSX and control groups were 249.40 ± 46.28 and 282.46 ± 55.78 µm, respectively. In a similar study by Goktas et al [15 ]using Spectralis, the reported value was 259.40 ± 33 µm in a group of patients whose average age was 75.3 years, although OPP was not calculated in that study.…”
Section: Discussionmentioning
confidence: 84%